2014
DOI: 10.1007/s11948-014-9603-3
|View full text |Cite
|
Sign up to set email alerts
|

Domesticating the Drone: The Demilitarisation of Unmanned Aircraft for Civil Markets

Abstract: Remotely piloted aviation systems (RPAS) or ‘drones’ are well known for their military applications, but could also be used for a range of non-military applications for state, industrial, commercial and recreational purposes. The technology is advanced and regulatory changes are underway which will allow their use in domestic airspace. As well as the functional and economic benefits of a strong civil RPAS sector, the potential benefits for the military RPAS sector are also widely recognised. Several actors hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 8 publications
0
54
0
1
Order By: Relevance
“…Here, the discourse of UAV regulations includes public safety and liability in case of an accident, societal benefits and stakeholders in international regulatory bodies such as the European Commission [40], rule-guided risks and opportunities of UAV [44], ethical tolerability [45], and effects upon privacy and other civil liberties [46]. The latter mentioned authors further used self-reported material of representatives of different drone sectors (including civil aviation authorities and data protection authorities) to study perspectives on privacy, data protection and ethical aspects [47].…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, the discourse of UAV regulations includes public safety and liability in case of an accident, societal benefits and stakeholders in international regulatory bodies such as the European Commission [40], rule-guided risks and opportunities of UAV [44], ethical tolerability [45], and effects upon privacy and other civil liberties [46]. The latter mentioned authors further used self-reported material of representatives of different drone sectors (including civil aviation authorities and data protection authorities) to study perspectives on privacy, data protection and ethical aspects [47].…”
Section: State Of the Artmentioning
confidence: 99%
“…significant gaps in the industry's knowledge about their privacy, data protection and ethical obligations under European and national laws" and that the legislation regarding these concerns lacks tremendously [47]. Interestingly, Boucher [40] showed another example of non-compliance. The authors conclude that the strategies to manage public acceptance in the European roadmap [48]) do not conform with the European concept of responsible research and innovation [49].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…It checks each predecessor in the (immediate) predecessor list of the currently visited task. If it is contained in the new sequence, then it shall be removed from the list (lines [3][4][5][6][7][8][9][10]. If the list of predecessors of the currently visited task is empty, then this task is ready to be moved into the new sequence (lines 11-15)-the task is added at the end of the sequence (line 12).…”
Section: Overall Availability Check (Lines 4-18)mentioning
confidence: 99%
“…Most of the UAVs commercially available so far have the capability of operating in an outdoor environment [1,47]. Previously, UAV applications used to be limited for only military purposes, but nowadays the situation has changed [8]. UAV emerges as a viable, low-cost technology [42] for use in various indoor applications [38].…”
Section: Introductionmentioning
confidence: 99%